Building Information Modeling (BIM) Implementation For Low Carbon – Eco Friendly Housing - Anjar Primasetra; Siswanti Zuraida; Muhammad Arief Irfan (Department of Architecture Universitas Muhammadiyah Jakarta, 2022)
Housing development in Indonesia is increasing annually and leads to the high demand of housing provision. In this recent time, Indonesian government facing housing backlog until 13,5 million. To solve this problem, the government then focus on housing regulation by implemented One Million Housing program from 2015. In one hand, this regulation is effective to solve housing backlog but in term of environmental awareness, this massive development leads to increasing of carbon emission. The impact is due to the building material and construction process that far from eco-friendly. For this reason, a solution is needed to reduce the environmental impact that occurs. One of the solutions that can be done is to develop a low-carbon housing design by using alternative materials that are environmentally friendly. Building Information Modelling (BIM) is one method to give a broad view regarding carbon emission of housing by integrative design modelling. This study then aims to analyze housing prototype of type 36 with low carbon emission. In this study, the material alternative for housing is light weight concrete panel by using plastic waste. The result show that the design alternative that proposed in this study is decreasing carbon emission as amount of 26% compared to conventional housing. The panel with 1 cm thickness has value of emission carbon as amount 2.56 tCO2e, is lower than conventional wall panel.